Pengembangan Sistem Deteksi CCTV Pintar untuk Meningkatkan Keamanan dan Keselamatan Pengguna Jalan Tol - Sri Bintan (Repeater : Publikasi Teknik Informatika dan Jaringan, 2025)
The safety and security of toll road users is a very important issue in road infrastructure management. In order to improve monitoring and response to potential dangers, smart CCTV technology can be an effective solution. This research aims to develop a smart CCTV detection system that can detect events that endanger safety, such as accidents or traffic disturbances. This system uses image processing technology and artificial intelligence to analyze CCTV footage in real-time and provide immediate warnings to security officers. Test results show that this system can detect events quickly and accurately, improving response and decision making to improve toll road safety. This system also allows for more efficient monitoring by reducing reliance on manual monitoring.